Mucoepidermoid Carcinoma of the Palatine Tonsil - Lucas Novaes Teixeira; Victor Angelo Martins Montalli; Luiz Carlos Santana Teixeira; Fabrício Passador-Santos; Andresa Borges Soares; Vera Cavalcanti de Araújo (Case Reports in Oncological Medicine)
Mucoepidermoid carcinoma (MEC) is the most common primary salivary gland malignancy in both adults and children. It has a slight female predilection and usually presents as a painless, rubber-like or soft mass, which may be fixed or mobile. Histologically, MEC is comprised of a mixture of cell types including mucous, epidermoid, and intermediate cells that can be arranged in solid nests or cystic structures. In the oral cavity, it most frequently occurs at the palate or buccal mucosa. The present paper aimed to describe an unusual case of MEC arising in the palatine tonsil.